Gut microbes and metabolites as modulators of blood-brain barrier integrity and brain health. (3rd March 2020) - Parker, Aimée; Fonseca, Sonia; Carding, Simon R.
ABSTRACT: The human gastrointestinal (gut) microbiota comprises diverse and dynamic populations of bacteria, archaea, viruses, fungi, and protozoa, coexisting in a mutualistic relationship with the host. When intestinal homeostasis is perturbed, the function of the gastrointestinal tract and other organ systems, including the brain, can be compromised. The gut microbiota is proposed to contribute to blood-brain barrier disruption and the pathogenesis of neurodegenerative diseases. While progress is being made, a better understanding of interactions between gut microbes and host cells, and the impact these have on signaling from gut to brain is now required. In this review, we summarise current evidence of the impact gut microbes and their metabolites have on blood-brain barrier integrity and brain function, and the communication networks between the gastrointestinal tract and brain, which they may modulate. We also discuss the potential of microbiota modulation strategies as therapeutic tools for promoting and restoring brain health.